Physical and mental exercise to create new congenial neurons, to increase intelligence and the role of ICTs. - Vouglanis, Taxiarchis; Driga, Anna Maria; Drigas, Athanasios (Technium BioChemMed, 2022)
Sports activities offer significant benefits to the human body. In addition to the physical benefits that exercise offers, it also provides mental benefits because the human brain is practiced to meet the needs of the sports. The human brain is the one that activates the members of the human body to make the necessary movements. However, over time the brain is not limited to this function but exerts itself on choosing the right movements that will help in taking a specific path to the sport that will lead to an even better performance. This is more visible in games and sports that do not require physical movement like chess. In such games, the athlete is not limited to performing movements but the brain is constantly working because it has to memorize certain movements, remember them, use them in the right order, while calculating the movements of the opponent. Consequently, sports activities offer a strong mental practice to the person involved in the exercise by increasing his or her intelligence, which is used to achieve better performance. The improvement of intelligence is also evident by the fact that the athlete is able to use the moves that are considered best in different situations at different times and with different opponents by appropriately adapting their technique.